Cost-savings for biosimilars in the United States: a theoretical framework and budget impact case study application using filgrastim. (4th July 2018) - Grewal, Simrun; Ramsey, Scott; Balu, Sanjeev; Carlson, Josh J.
ABSTRACT: Background : Biosimilars can directly reduce the cost of treating patients for whom a reference biologic is indicated by offering a highly similar, lower priced alternative. We examine factors related to biosimilar regulatory approval, uptake, pricing, and financing and the potential impact on drug expenditures in the U.S. Methods : We developed a framework to illustrate how key factors including regulatory policies, provider and patient perception, pricing, and payer policies impact biosimilar cost-savings. Further, we developed a budget impact cost model to estimate savings from filgrastim biosimilars under various scenarios. The model uses publicly available data on disease incidence, treatment patterns, market share, and drug prices to estimate the cost-savings over a 5-year time horizon. Results : We estimate five-year cost savings of 256 million, of which 18% (47 million) are from reduced patient out-of-pocket costs, 34% (86 million) are savings to commercial payers, and 48% (123 million) are savings for Medicare. Additional scenarios demonstrate the impact of uncertain factors, including price, uptake, and financing policies. Conclusions : A variety or interrelated factors influence the development, uptake, and cost-savings for Biosimilars use in the U.S. The filgrastim case is a useful example that illustrates these factors and the potential magnitude of costs savings.